Method of telecommunication channel performance improvement by complex use of pseudo noise coding sequences - Плющ, Олександр Григорович (Science-based technologies, 2020)
The paper proposes an approach to design of noise immune and concealed data transmission channel in telecommunication networks. The approach is based on performing spectrum spreading of the useful information bits, as well as its additional scrambling. For this purpose, pseudo noise coding sequences are used derived from the primitive polynomials of the order eight and fifteen, which possess good auto and inter correlational properties. It is studied performance of the telecommunication channel that includes frames of 128 bit length, each of which is spectrally spread 256 times with the help of a synthesized pseudo noise coding sequence. The second 32768 chip-long pseudo noise coding sequence is used to mark the frame duration and perform additional information scrambling. To ensure maximum protection from interception, the paper proposes to use ten long pseudo noise sequences with 128 cyclic shifts and four short pseudo noise coding sequences. In this case, it is conceived to form  5120 different combinations - «short pseudo noise coding sequence – long pseudo noise coding sequence – cyclic shift of the long pseudo noise sequence», or triplets, transitions between which are performed on a frame-by-frame basis. Transition rules can be defined by a certain algorithm or beforehand known transition table. Both the algorithm and the table can undergo changes from time to time. To assess performance of the designed telecommunication channel, computer simulation was used. With account of the simulation results, the inference is made that the processing of the additive mixture of the desired signal and interfering ones, which surpass the desired signal two times in terms of power, by the matched filters permits to confidently reveal the information frame structure being transmitted by determining frame beginning pulse and establish the bit values of the desired information. Research findings, obtained in this paper, permit to claim that the designed telecommunication channel, with complex use of the ten long pseudo noise coding sequences with cyclic shifts and four short pseudo noise coding sequences can be successfully used for implementation in noise immune concealed telecommunication networks